The Lived Experiences of Intermediate Teachers in Fostering Engagement in English Classes Through Blended Learning - Cidro, Mark Gleen (International Journal of Language and Literary Studies, 2023)
The pandemic has brought several impacts in the field of education. Among the subjects that have been challenged in developing communicative competence in the new normal is English. Thus, this study aimed to explore the lived experiences of 15 Grade Four English Teachers in the Philippines to understand better how they concerted all efforts to engage students in English classes through the blended learning platform. The data were gathered by employing a phenomenological investigation, a qualitative inquiry. Through several in-depth interviews, in-person classroom observations, document analyses, data were coded and analyzed thematically. Findings showed that Fourth Grade teachers were able to engage their students during in-person sessions through the following themes (1) varied, (2) experiential, (3) animation, (4) reinforcement, and (5) reflection. As for the asynchronous sessions, the study found out that students wanted activities that are (1) varied, (2) challenging, (3) imaginative, (4) authentic, (5) rewarding, and (6) forges partnership. With these data, development programs for teachers to foster student engagement in English classes through the Blended Learning platform were recommended.